Geothermal Energy Resource Assessment of Parts of Alaska. Final Report - Wescott, E. M.; Turner, D. L.; Kienle, J. (University of Alaska Fairbanks, 1982)
The central Seward Peninsula was the subject of a geological, geophysical and geochemical reconnaissance survey during a 30-day period in the summer of 1980. The survey was designed to investigate the geothermal energy resource potential of this region of Alaska. A continental rift system model was proposed to explain many of the Late Tertiary-to-Quaternary topographic, structural, volcanic and geothermal features of the region. Geologic evidence for the model includes normal faults, extensive fields of young alkalic basalts, alignment of volcanic vents, graben valleys and other features consistent with a rift system active from late Miocene time to the present. Five traverses crossing segments of the proposed rift system were run to look for evidence of structure and geothermal resources not evident from surface manifestation. Gravity, helium and mercury soil concentrations were measured along the traverses. Seismic, resistivity, and VLF studies are presented.